BUSINESS EXPANSION: A LITERATURE REVIEW ON FRANCHISING AND BRAND LICENSING - Diego Weber dos Santos, Jean (Revista Gênero e Interdisciplinaridade, 2026)
This article presents a literature review on business expansion strategies, with a special focus on franchising and brand licensing models. The analysis covers the main theories that underlie corporate expansion, including Agency Theory, Transaction Cost Theory, and the Uppsala Model of internationalization. The objective is to consolidate existing knowledge, identify the advantages and disadvantages of each model, and point out directions for future research. The review demonstrates that, while franchising is a robust strategy for rapid market penetration and geographic growth with limited capital, brand licensing offers a flexible pathway to leverage brand value and intellectual property. The choice of the optimal strategy depends on a complex interaction among company resources, market conditions, and long-term strategic objectives. The research concludes that both strategies are vital for sustainable growth in competitive global markets.